Pulse pressure amplification and its determinants. (2nd January 2016) - Pichler, Gernot; Martinez, Fernando; Vicente, Antonio; Solaz, Elena; Calaforra, Oscar; Redon, Josep
Abstract : Background . Pulse pressure (PP) amplification expressed as the peripheral-to-central PP ratio has gained importance in the assessment of cardiovascular phenotypes and cardiovascular risk. The aim of the present study was to assess the relationship between PP amplification, large vessel parameters and peripheral blood pressure (BP) to gain insights into the amplification phenomenon. Methods . Peripheral BP, central BP and carotid-femoral pulse wave velocity (cfPWV) were assessed using the OMRON M6, SphygmoCor and Complior devices, respectively, in 741 adults attending the hypertension outpatient clinic. Analysis of covariance, partial correlations and multiple linear regression models were performed to assess the relationship between PP amplification, peripheral BP and cfPWV. Results . PP amplification was inversely related to BP group. Women showed lower PP amplification than men (1.24 ± 0.18 and 1.35 ± 0.18, respectively, p < 0.001). Age, female gender and mean arterial pressure were inversely associated with PP amplification ( p < 0.001), whereas heart rate and body mass index showed positive associations ( p < 0.001 and p = 0.049, respectively). cfPWV was a predictor of PP amplification in men but not in women ( p = 0.006 and p = 0.424, respectively). Conclusions . PP amplification is related to BP: the higher the BP, the lower the PP amplification. Gender, age and body composition have a significant impact on PP amplification.